Students’ Difficulties in Writing Narrative Text - Nensi Fadilah; Amalia Hasanah; Winny Agustia Riznanda (Jadila: Journal of Development and Innovation in Language and Literature Education, 2024)
Writing English is not easy to do by students. Students will face several difficulties regarding that issue. Thus, this study aimed to find out the tenth grade students’ difficulties in writing narrative text at SMAN 19 Palembang. This study used the qualitative method of a case study. This study was conducted at SMAN 19 Palembang, by using a purposive sampling technique. The data collection technique used was an interview. Interviews were conducted with six students who had difficulty writing narrative texts in the tenth grade at SMAN 19 Palembang. The data obtained from interviews, then analyzed using thematic analysis. This study showed that most students had difficulty writing narrative texts. Difficulty classifications that have been done by students include generic structures, such as, orientation, complication, resolution and re- orientation. Besides the generic structure, students also experience difficulties in grammar, past tense, pronouns, prepositions, composing words, "to be, vocabulary, and punctuation.